Acute Liver Failure Due to Budd‐Chiari Syndrome in the Setting of Cardiac Synovial Sarcoma. Issue 3 (April 2015) - Stine, Jonathan G.; Newton, Kelly; Vinayak, Ajeet G.
Abstract : N/A: Primary malignant tumors of the heart, specifically cardiac sarcomas, are rare and mainly diagnosed at autopsy. Acute Budd‐Chiari syndrome is a recognized cause of acute liver failure and has been associated with several rare cardiac tumors: atrial myxoma, caval rhabdomyosarcoma, and primary cardiac adenocarcinoma. We present the first case of a fatal, highly differentiated cardiac synovial sarcoma that presented as acute liver failure from Budd‐Chiari syndrome.